CTNI-37. ISOEFFECTIVE HYPOFRACTIONATION FOR ELDERLY OR FRAIL PATIENTS WITH A NEWLY DIAGNOSED GLIOBLASTOMA: A POOLED INTERNATIONAL STUDY. (12th November 2021) - Perlow, Haley; Yang, Michael; Klamer, Brett; Matsui, Jennifer; Marrazzo, Livia; Detti, Beatrice; Scorrsetti, Marta; Clerici, Elena; Arnett, Andrea; Beyer, Sasha; Ammirati, Mario; Chakravarti, Arnab; et al.
Abstract: PURPOSE: The standard of care (SOC) for elderly or frail glioblastoma (GBM) patients is 40 Gy in 15 fraction radiotherapy. However, this regimen has a lower BED compared to the Stupp regimen, 60 Gy in 30 fractions. We hypothesize that isoeffective hypofractionated radiation of 52.5 Gy in 15 fractions (BED equivalent to Stupp) will have superior survival compared to standard of care. METHODS: Elderly GBM patients treated with 52.5 Gy in 15 fractions were pooled from 2 phase II studies, 1 phase 1 and a prospective observation study. Overall survival (OS) and progression free survival (PFS) were defined as the time elapsed between surgery/biopsy and death from any cause or progression. Univariate and multivariate analyses were performed. RESULTS: 62 newly-diagnosed patients were eligible for this analysis. Median follow-up was 10 months. The median OS and PFS was 10.3 and 6.9 mos, respectively. Patients with KPS ≥ 70 and < 70 had a median OS of 15.3 and 9.5 mos. No survival difference was seen between unmethylated and methylated patients with a median OS of 10.2 and 10.3 months, respectively. Multivariable analysis demonstrated that concurrent chemotherapy was an independent prognostic factor for improved PFS and OS. Grade 3 neurologic toxicity was seen in 2 patients (3.2%). CONCLUSION: This is the first pooled, prospective analysis of elderly/frail GBM patients treated with dose-escalated hypofractionated radiation. Treatment was well tolerated and demonstrated excellent OS and PFS, exceeding that from prior elderly trials (Roa; 6.5 mo [poor KPS]/Perry; 9.3mo [good KPS]). This treatment regimen gives the elderly population an alternative to Stupp that is not de-escalating therapy. Future prospective trials are needed to validate these results.